Problem solving at secondary school level: a cognitive and social change - Consuelo Escudero; Sonia González de Flores (Investigações em Ensino de Ciências, 1996)
This paper reports our first studies on problem solving at secondary school level, with low performance students, under the framework of the integration of two meanings of the constructivist conception: a) the construction of meaning and content’s role, and b) the integration of individual and social aspects. In classroom problem solving in 3rd year (15 years old) just very elementary signs of operationalism were observed; the use of formulae appeared only when students had a certain level of content mastery. The limited meaning students assign to the equality sign and its symbolical representation constitutes another important nucleus of difficulty detected in this research. This analysis and its interpretation are used for some educational suggestions.